Deep water formation in the North Pacific and deglacial CO2 rise. (27th June 2014) - Rae, James W. B.; Sarnthein, Michael; Foster, Gavin L.; Ridgwell, Andy; Grootes, Pieter M.; Elliott, Tim
Abstract Deep water formation in the North Atlantic and Southern Ocean is widely thought to influence deglacial CO2 rise and climate change; here we suggest that deep water formation in the North Pacific may also play an important role. We present paired radiocarbon and boron isotope data from foraminifera from sediment core MD02‐2489 at 3640 m in the North East Pacific. These show a pronounced excursion during Heinrich Stadial 1, with benthic‐planktic radiocarbon offsets dropping to 350 years, accompanied by a decrease in benthic δ11B. We suggest that this is driven by the onset of deep convection in the North Pacific, which mixes young shallow waters to depth, old deep waters to the surface, and low‐pH water from intermediate depths into the deep ocean. This deep water formation event was likely driven by an increase in surface salinity, due to subdued atmospheric/monsoonal freshwater flux during Heinrich Stadial 1. The ability of North Pacific Deep Water (NPDW) formation to explain the excursions seen in our data is demonstrated in a series of experiments with an intermediate complexity Earth system model. These experiments also show that breakdown of stratification in the North Pacific leads to a rapid 30 ppm increase in atmospheric CO2, along with decreases in atmospheric δ13C and Δ14C, consistent with observations of the early deglaciation. Our inference of deep water formation is based mainly on results from a single sediment core, and our boron isotope data are unavoidably sparse in the key HS1 interval, so this hypothesis merits further testing. However, we note that there is independent support for breakdown of stratification in shallower waters during this period, including a minimum in δ15N, younging in intermediate water 14C, and regional warming. We also re‐evaluate deglacial changes in North Pacific productivity and carbonate preservation in light of our new data and suggest that the regional pulse of export production observed during the Bølling‐Allerød is promoted by relatively stratified conditions, with increased light availability and a shallow, potent nutricline. Overall, our work highlights the potential of NPDW formation to play a significant and hitherto unrealized role in deglacial climate change and CO2 rise.